A NEW APPROACH TO THE ELECTRONIC-STRUCTURE OF 2-DIMENSIONAL DISORDERED ALLOYS - Demello, D. F.; Cabrera, G. G. (Elsevier B.V., 1995)
We propose a novel method to calculate the electronic Density of States (DOS) of a two dimensional disordered binary alloy. The method is highly reliable and numerically efficient, and Short Range Order (SRO) correlations can be included with no extra computational cost. The approach devised rests on one dimensional calculations and is applied to very long stripes of finite width, the bulk regime being achieved with a relatively small number of chains in the disordered case. Our approach is exact for the pure case and predicts the correct DOS structure in important limits, such as the segregated, random, and ordered alloy regimes. We also suggest important extensions of the present work.
Keywords: DISORDERED SYSTEMS; ELECTRONIC STATES (LOCALIZED); ORDER-DISORDER EFFECTS